GAMBARAN KOMPONEN YANG MEMPENGARUHI KEPUTUSAN MEMBELI HANDPHONE BLACKBERRY DAN GAYA HIDUP KONSUMEN - Marolla, Siti Fauziah Hanim (CALYPTRA : Jurnal Ilmiah Mahasiswa Universitas Surabaya, 2013)
Research is aimed to describe what component most dominated in influencing consumers buying the BlackBerry, and want to describe consumer groups whose lifestyle may as what is most cell phones brand BalckBerry, buy a product which a later described components of the decision of the purchase of the most influence the behavior of consumer in deciding buy cell phone BlackBerry to a style of living. The result showed that of the seven of the components that the eliminated into five components through a survey early it appears that components is most dominated consumers buy a cell phone in the resolution of the BlackBerry there are three components into components most influence the decision of the purchase of the BlackBerry, which is a type of peoduct brands and place its sales agent. While to the delineation of lifestyle there are three lifestyle is the most dominant imaged fulfilleds, achievers and experiencer.